1994
DOI: 10.1152/jn.1994.71.3.1285
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements modulate activity in hippocampal, parahippocampal, and inferotemporal neurons

Abstract: 1. Inferotemporal, hippocampal, and parahippocampal units were recorded while monkeys were alert (as judged by eye movements) but resting, in both light and dark. 2. Spontaneous saccadic eye movements produced significant changes in unit activity for 108 of 308 cells. This activity is shown to be extraretinal either because it occurred in complete darkness or because of its timing relative to the eye movement. 3. The total saccadic modulation in the ventral temporal lobe is estimated to be over ten million act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 0 publications
9
71
0
2
Order By: Relevance
“…Based on this analysis, the spike patterns of 58 (44%) of 131 single units were predictable across individual saccades to a degree that was significantly greater than chance (test of proportions, P < 0.01). This proportion is in agreement with previously reported saccadic modulation in the monkey medial temporal lobe (MTL) (23,24). In addition, we compared the incidence of saccade-modulated neurons with that of neurons that were significantly responsive to the onset of visual stimuli (16), and we found no correlation between the two distributions (Spearman's rank correlation coefficient, ρ = 0.09; P > 0.1), indicating that the tendency of neurons to show saccade modulation was not simply a reflection of visual sensitivity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Based on this analysis, the spike patterns of 58 (44%) of 131 single units were predictable across individual saccades to a degree that was significantly greater than chance (test of proportions, P < 0.01). This proportion is in agreement with previously reported saccadic modulation in the monkey medial temporal lobe (MTL) (23,24). In addition, we compared the incidence of saccade-modulated neurons with that of neurons that were significantly responsive to the onset of visual stimuli (16), and we found no correlation between the two distributions (Spearman's rank correlation coefficient, ρ = 0.09; P > 0.1), indicating that the tendency of neurons to show saccade modulation was not simply a reflection of visual sensitivity.…”
Section: Resultssupporting
confidence: 93%
“…Because the timing of neuronal spikes in the hippocampus is influenced by theta oscillations (9,(44)(45)(46), theta phase resetting could represent a mechanism by which stimulus-related activity in the hippocampus, in the form of neuronal firing, may be coordinated with ongoing behavior to optimize memory formation. Previous studies of saccadic modulation in the primate hippocampus have drawn parallels between this modulation and theta activity in rodents (24,47). Saccadic eye movements partition sensory input into discrete elements in much the same way that whisking and sniffing, behaviors often associated with hippocampal theta in rodents, break up somatosensory and olfactory information, respectively (1).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, investigations of the effects of fiber-sparing neurotoxic lesion of these cortical areas will be necessary to ascertain whether or not the item-specific recognition impairment after areas TH/TF could be associated with indirect, even relatively small, transection of fibers traveling from visual areas V4 and TE to PRh more rostrally (Suzuki, 1996). In addition, given that saccadic eye movements (even in complete darkness) modulate TH/TF neuron activity (Ringo et al, 1994;Nowicka et al, 1995;Sobotka et al, 1997), it remains possible that the increase in saccadic eye movements found after TH/TF lesions could have affected the way in which the operated monkeys …”
Section: Parahippocampal Cortex (Th/tf) and Recognition Memorymentioning
confidence: 99%
“…Ringo et al (1994) and Sobotka et al (1997) have described modulation by eye movement in the activity of the inferior and medial temporal cortical neurons. The work of Scheinberg and Logothetis (2001) has recently focused on natural vision (with its rich repertoire of SEM) and the activity of IT cells.…”
Section: Discussionmentioning
confidence: 99%